2022
DOI: 10.3389/fmed.2021.814496
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis—From Mechanisms of Injury to Modulation of Disease

Abstract: The Transregional Collaborative Research Center “Organ Fibrosis: From Mechanisms of Injury to Modulation of Disease” (referred to as SFB/TRR57) was funded for 13 years (2009–2021) by the German Research Council (DFG). This consortium was hosted by the Medical Schools of the RWTH Aachen University and Bonn University in Germany. The SFB/TRR57 implemented combined basic and clinical research to achieve detailed knowledge in three selected key questions: (i) What are the relevant mechanisms and signal pathways re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 208 publications
(279 reference statements)
0
17
0
1
Order By: Relevance
“…(3) Our work can recommend polarizing microscope as a tool to evaluate fibrosis of ovary and oviducts, as it is a cheap, less bulky, and user friendly tool. (4) Polarizing microscope can differentiate between different collagen patterns, as mature thick type I collagen appeared with orange to red color, while thin immature collagen type III was green in color. However, studies are still needed to be able to recommend polarizing microscopy for demonstrating of fibrosis in different organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Our work can recommend polarizing microscope as a tool to evaluate fibrosis of ovary and oviducts, as it is a cheap, less bulky, and user friendly tool. (4) Polarizing microscope can differentiate between different collagen patterns, as mature thick type I collagen appeared with orange to red color, while thin immature collagen type III was green in color. However, studies are still needed to be able to recommend polarizing microscopy for demonstrating of fibrosis in different organs.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is commonly demonstrated in different organs as heart, kidney, lungs, liver, and testis. Without effective treatment, fibrosis impaired organ function and ultimately induces organ malfunction [1][2][3][4] . Fibrosis is characterized by excessive scaring formation instead of normal tissue, which then finally results in the destruction of the tissue architecture and organ remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune hepatitis is the second leading cause of liver damage in SS patients [ 47 ]. Liver fibrotic processes depend on the activation of an initial injury of hepatocytes by autoreactive immunological phenomena; these events lead to the proliferation of myofibroblasts and the activation of stellate cells [ 48 ]. These manifestations may, in turn, accelerate the deposition of collagen or glycoproteins in the liver, leading to liver fibrosis that interferes with the liver function and contributes to gradual organ failure [ 49 ].…”
Section: Clinical Fibrotic Manifestation In Ssmentioning
confidence: 99%
“…32 In addition, hepatic fibrosis might be regulated by cytokines and chemokines. 45 IL-17 is an essential regulatory cytokine in liver inflammation, and γδ T cells accumulate in fibrotic livers and contribute to IL-17 secretion in chronic hepatitis patients. 46,47 A previous study revealed that in a Schistosoma japonicum-infected C57BL/6 mouse model, γδ T cells mediate the recruitment of neutrophils to the liver and induce liver fibrosis with IL-17 production.…”
Section: γδ T Cells and Hepatic Fibrosis Cirrhosismentioning
confidence: 99%
“…A study reported that a decrease in the number of γδ T cells in the peripheral blood and liver is significantly associated with the severity of fibrosis 32 . In addition, hepatic fibrosis might be regulated by cytokines and chemokines 45 . IL‐17 is an essential regulatory cytokine in liver inflammation, and γδ T cells accumulate in fibrotic livers and contribute to IL‐17 secretion in chronic hepatitis patients 46,47 .…”
Section: γδ T Cells and Hepatic Fibrosis Cirrhosismentioning
confidence: 99%